The occurrence of equatorial spread-F at conjugate stations in Southeast Asia - Klinngam, Somjai; Supnithi, Pornchai; Rungraengwajiake, Sarawoot; Tsugawa, Takuya; Ishii, Mamoru; Maruyama, Takashi (My University, 2015)
In this study, the probability of equatorial spread-F (ESF) occurrence at the conjugate stations in Southeast Asia: Chiangmai station (CMU), Thailand, and Kototabang station (KTB), Indonesia, and near the magnetic equator, Chumphon station (CPN), Thailand, is presented. We analyze the ionogram data recorded by the Frequency Modulated Continuous Wave (FM/CW) ionosondes for the periods of minimum solar activity from September 2008 to April 2009 and in the equinoctial months (March and April) from 2006 to 2013. The spread-F signatures are manually categorized into three types: the frequency spread-F (FSF), the range spread-F (RSF) and the mixed spread-F (MSF) and the monthly average percentage of the occurrence of each ESF type is presented. The results show that the percentage of RSF occurrence at CPN, which is located around the magnetic equator, is higher than at other stations and the RSF mostly occurs during the equinoctial months. On the other hand, the FSF occurrence at CMU and KTB, that are located in the northern and southern hemispheres, respectively, are higher than at CPN. The RSF occurrence typically has the peaks before midnight, while the maximum occurrence rate of FSF is after midnight. Furthermore, the RSF onsets normally precede the FSF onsets by about 1-2 h. As the solar activity levels go up, the percentages of RSF occurrence increase, but the percentages of FSF tends to decrease. In addition, we compare the statistics of observed RSF occurrence with the prediction of the IRI-2012 model. The results show that the IRI model overestimates the observed RSF occurrence at all stations during most of the solar activity levels and seasons, except in June 2008 (21:00-03:00 LT), March 2011 (23:30-01:00 LT) and March 2013 (01:00-02:30 LT) when the IRI model underestimates our observations. However, the IRI model gives closer probability of RSF occurrence to our observed values at CPN, especially in equinoctial months and during the periods of medium solar activity. This work is important for an improvement of the IRI model in the prediction of the spread F occurrence probability in the low-latitude region.
Keywords: Conjugate stations; Equatorial spread-Rffrt; IRI model; Solar activity